Tracking the evolution of cancer genomes - Sun, H (2023)
Tumour clones consist of cancerous cells with shared ancestry. The study of cancer evolution has been further advanced by the introduction of mathematical algorithms to reconstruct the phylogenetic tree within the tumour. Bulk sequencing data pro- vides not only the VAF and ploidy information that most established methods now use to infer tumour subclonal structure, but also another equally important piece of information, namely phasing information. Phasing information from sequencing reads can be used to find the most likely phylogenetic trees.